ANALISIS MOTIVASI, LOYALITAS DAN PRODUKTIVITAS KINERJA PEGAWAI YANG MEMPENGARUHI TERHADAP KEPEMIMPINAN KEPALA DESA BRUJUL, KECAMATAN JATEN KABUPATEN KARANGANYAR TAHUN 2021 - Novitasari, Intan Tri; Sulistyo, Sulistyo (Surakarta Management Journal, 2021)
Leadership is a crucial aspect of management in every organisation or institution. This research assessed an organization's capacity to lead effectively, which will decide whether it succeeds or fails in achieving its objectives. A leader must have the proper influence to lead the members of his organisation in this endeavour. The purpose of this study is to examine how employee motivation, loyalty, and productivity impact the leadership of the Headman of Brujul Village, Jaten Sub-District, Karanganyar District. This type of research is a qualitative case study that describes the interaction data analysis from the withdrawal of all population data utilised as a sample. Interviews, observations, and documents were used to collect data in this study. The outcomes of this study show that the village headman's leadership position has a significant impact on staff motivation, loyalty, and productivity at the Brujul Village Office, Jaten Sub-District, Karanganyar District. The community's interests, in this case the employees', will be served by creating decent working circumstances, which will aid them in carrying out their responsibilities. As a result, employees will be able to make the most of their time and remain loyal to the company. The motivation to attempt as much as possible will emerge, accompanied by a spirit of working under unusual circumstances. If the leader or village headman ensures the health of employees by restricting working hours or reducing extra hours, employees' health can be maintained. Employees who perform efficiently and effectively in line with processes will have a positive impact on job productivity.